2023
DOI: 10.1002/hbm.26536
|View full text |Cite
|
Sign up to set email alerts
|

Functional network dynamics revealed by EEG microstates reflect cognitive decline in amyotrophic lateral sclerosis

Marjorie Metzger,
Stefan Dukic,
Roisin McMackin
et al.

Abstract: Recent electroencephalography (EEG) studies have shown that patterns of brain activity can be used to differentiate amyotrophic lateral sclerosis (ALS) and control groups. These differences can be interrogated by examining EEG microstates, which are distinct, reoccurring topographies of the scalp's electrical potentials. Quantifying the temporal properties of the four canonical microstates can elucidate how the dynamics of functional brain networks are altered in neurological conditions. Here we have analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…The right precentral gyrus, left postcentral gyrus and supplementary motor area were identi ed as higher contributors of microstates A, B and D, respectively. These microstates all demonstrated altered temporal characteristics in ALS, as indicated in previous research [3]. A higher contribution may seem counterintuitive, considering the atrophy commonly observed in the somatosensory cortex in ALS [27].…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The right precentral gyrus, left postcentral gyrus and supplementary motor area were identi ed as higher contributors of microstates A, B and D, respectively. These microstates all demonstrated altered temporal characteristics in ALS, as indicated in previous research [3]. A higher contribution may seem counterintuitive, considering the atrophy commonly observed in the somatosensory cortex in ALS [27].…”
Section: Discussionsupporting
confidence: 74%
“…2) partly corresponded as the right superior occipital lobe seemed to be involved in generating microstate class B, with the addition of fronto-temporal areas. Both microstates A and B are likely to represent the activation of sensory networks, especially considering their modulations in multiple sclerosis [25] and in movement disorders such as ALS [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on resting‐state EEG microstates have identified four distinct categories, microstates A, B, C, and D, which have shown high similarity across different studies (Tarailis et al, 2023 ). Nevertheless, the parameters and topography of these microstates were associated with various factors, including neurological and psychiatric disorders, age, and cognitive processes (Khanna et al, 2015 ; Metzger et al, 2023 ). Additionally, research has explored the correlation between resting‐state EEG microstates and resting‐state fMRI (Britz et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%